Vertical jump performance in Italian male and female national team soccer players - Castagna, C.; Castellini, E. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to examine the validity of vertical jump (VJ) performance variables in elite-standard male and female Italian soccer players. One hundred eighteen national team soccer players (n = 56 men and n = 62 women) were tested for countermovement (CMJ) and squatting jump (SJ) heights. The stretch-shortening cycle efficiency (SSCE) was assessed as percentage of CMJ gain over SJ (dCMJ-SJ), difference (CMJ-SJ), and ratio (CMJ:SJ). Results showed significant sex difference in SJ and CMJ. Differences in SSCE were mainly in the absolute variables between sexes. Cutoff values for CMJ and SJ using sex as construct were 34.4 and 32.9 cm, respectively. No competitive level differences in VJ performance were detected in the male players. Female national team players showed VJ performance higher than the under 17 counterpart. The results of this study showed that VJ performance could not discriminate between competitive levels in male national team-selected soccer players. However, the use of CMJ and SJ normative data may help strength and conditioning coaches in prescribing lower limb explosive strength training in elite soccer players. In this, variations in VJ performance in the range of approximately 1 cm may be regarded as of interest in tracking noncasual variation in elite-standard soccer players.